Nurturing wellbeing amidst the climate crisis: on the need for a focus on wellbeing in the field of climate psychology - Isham, Amy; Morgan, Gareth; Kemp, Andrew Haddon (Frontiers in Psychology, 2023)
Awareness of climate change can prompt overwhelming emotions that threaten wellbeing such as anger, despair, and anxiety. Neoliberal views of human beings and their mental health strip the individual from their social and material context, driving personal dissatisfaction, social isolation, and ecological destruction. In this piece, we contend that advancements in scholarly research on wellbeing offer valuable insights for addressing the challenges posed by the climate crises while respecting human wellbeing. Such frameworks, which include the Power Threat Meaning Framework (PTMF) and the GENIAL model, emphasise the interconnected nature of people, communities, and their environment. In turn, they help to lay the groundwork for the development of 'post-growth' societies focused on supporting outcomes such as human wellbeing, social justice, and environmental regeneration. There are a number of different actions that practitioners and even lay individuals can take to promote positive outcomes and effective responses in the face of the climate crisis. These actions, discussed in the concluding sections of the article, aim to foster wellbeing and impactful engagement with the challenges posed by climate change.